PERBANDINGAN KEBOCORAN TEPI ANTARA RESTORASI RESIN KOMPOSIT TIPE BULK-FILL DAN TIPE PACKABLE DENGAN PENGGUNAAN SISTEM ADHESIF TOTAL ETCH DAN SELF ETCH - Arlina Nurhapsari (Faculty of Dentistry, Universitas Islam Sultan Agung, 2016)
Background: Composite resin has been widely used because of it's great aesthetic and physico-chemical properties. Type of posterior composite resins mostly used nowadays are packable and bulk-fill composite resins. Shrinkage in composite resin resulting microleakage that could lead to pulp sensitivity. Dentin bonding adhesive system can help to minimalize shrinkage. There are two type of adhesive system, the total etch and self etch group. The purpose of this study was to compare the microleakage between bulk-fill and packable composit resin with two different types of dentin bonding adhesive system. Method: twenty premolar teeth used as sample. The teeth were divided into four groups of 5 teeth each and Class I cavity preparations were prepared. The groups are : G1 (PC + TE), G2 (PC + SE), G3 (BC + TE), G4 (BC + SE). The specimens were thermocycled, stained with methylene blue dye, and sectioned to evaluate the dye penetration.Result: Kruskal Wallis test showed no difference among 4 groups. Meanwhile, Mann Whitney test showed significance difference between G2 - G3, and G3 - G4.Conclus/on: The study demonstrated that total etch has better sealing ability than self etch and there was no significant microleakage difference between bulkfill composite and packable composite.